Grain dust explosions - record low In 1992 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
A record low, six grain dust explosions were reported in the U.S. for 1992 according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Consultant and Professor Emeritus, Kansas State University. This compares to 12 in 1991 and a ten-year average of 15 explosions.
Keywords: Grain dust; Dust explosions